Reinterpreting Musyāhadah and Tajallī in Surah Ar-Rūm (Verses 8, 21, and 22): Abdullah Saeed’s Contextual Approach for Multicultural Islamic Education - Iwan Kurniawan. ZP; Zahro Rokhmawati; Renny Dwi Arumsari; Zaenal Abidin; Mohammad Affan; Devi Fatwanti (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
This study analyzes the concepts of musyāhadah (inner witnessing) and tajallī (Divine manifestation) in Surah Ar-Rūm (30): 8, 21, and 22, and critically examines their contextualization within multicultural Islamic education. Employing a qualitative library research design, this study operationally applies Abdullah Saeed’s contextualist approach to bridge the text’s historical meaning with contemporary social challenges. The findings reveal that cosmic reflection (v. 8), relational tranquility (v. 21), and linguistic-racial diversity (v. 22) are not merely passive objects of theological contemplation, but active empirical loci where the Divine manifests (tajallī) and is spiritually internalised (musyāhadah). The discussion demonstrates that these concepts provide a radical epistemological shift from conventional, cognitive-moralistic models of character education toward a transformative paradigm that embraces pluralism as a living curriculum. The novelty of this study lies in its explicit contextualization of Sufi metaphysics to counter modern religious exclusivism, transforming the pinnacle of Sufi spiritual realization from isolated asceticism into an active social engagement. The implications suggest that integrating these concepts into contemporary Islamic education fosters a